Consumer acceptance of low-dose irradiated, boneless, pork chops - S E Luchsinger; Zepeda C.M. Garcia; Edgar IV Chambers; M E Hollingsworth; Melvin C Hunt; James L Marsden; Sally L Stroda; Canas E Rubio J; Curtis L Kastner; W G Kuecker; T Mata; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1995)
Acceptance of irradiated, chilled, boneless, pork chops and nonirradiated controls by consumers was not different. Coupled with consumer concerns about food safety and well-documented improvement in consumer attitudes about irradiated foods, the potential for market acceptance is very promising.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Irradiation; Consumer acceptance